Growth of calcium phosphate coating on Ti-7.5Mo alloy after anodic oxidation - Escada, A. L A [UNESP]; Machado, J. P B; Nakazato, Roberto Zenhei [UNESP]; Alves Claro, A. P R [UNESP] (Trans Tech Publications, 2013)
Titanium and its alloys are widely used as biomaterials due to their mechanical, chemical and biological properties. To enhance the biocompatibility of titanium alloys, various surface treatments have been proposed. In particular, the formation of titanium oxide nanotubes layers has been extensively examined. Among the various materials for implants, calcium phosphates and hydroxyapatite are widely used clinically. In this work, titanium nanotubes were fabricated on the surface of Ti-7.5Mo alloy by anodization. The samples were anodized for 20 V in an electrolyte containing glycerol in combination with ammonium fluoride (NH4F, 0.25%), and the anodization time was 24 h. After being anodized, specimens were heat treated at 450 °C and 600°C for 1 h to crystallize the amorphous TiO2 nanotubes and then treated with NaOH solution to make them bioactive, to induce growth of calcium phosphate in a simulated body fluid. Surface morphology and coating chemistry were obtained respectively using, field-emission scanning electron microscopy (FEG-SEM), AFM and X-ray diffraction (XRD). It was shown that the presence of titanium nanotubes induces the growth of a sodium titanate nanolayer. During the subsequent invitro immersion in a simulated body fluid, the sodium titanate nanolayer induced the nucleation and growth of nano-dimensioned calcium phosphate. It was possible to observe the formation of TiO2 nanotubes on the surface of Ti-7.5Mo. Calcium phosphate coating was greater in the samples with larger nanotube diameter. These findings represent a simple surface treatment for Ti-7.5Mo alloy that has high potential for biomedical applications. © (2013) Trans Tech Publications, Switzerland.
Keywords: Calcium phosphate; Nanotubes TiO2; Titanium alloys; Biomedical applications; Chemical and biologicals; Field emission scanning electron microscopy; Nanotube diameters; Nanotubes tio; Nucleation and growth; Simulated body fluids; Titanium oxide nanotubes; Anodic oxidation; Biocompatibility; Biological materials; Diffusion in liquids; Diffusion in solids; Medical applications; Molybdenum alloys; Nanotubes; Phosphate coatings; Sodium; Surface treatment; Titanium; Titanium compounds; Titanium oxides; X ray diffraction